Brill's companion to Thucydides - Rengakos, Antonios; Tsakmakis, Antonis (Brill's companions in classical studies., 2006)
This volume on Thucydides, the most important historian of the ancient world, comprises articles by thirty leading international scholars. The contributions cover a wide range of issues, including Thucydides' life, intellectual milieu and predecessors, Thucydides and the act of writing, his rhetoric, historical method and narrative techniques, narrative unity in the History, the speeches, Thucydides' reliability as a historian, and his legacy through the centuries. Other topics dealt with include warfare, religion, individuals, democracy and oligarchy, the invention of political science, Thucydides and Athens, Sparta, Macedonia/Thrace, Sicily/South Italy, Persia, and the Argives. The volume aims to provide a survey of current trends in Thucydidean studies which will be of interest to all students of ancient history.